Perbedaan Kepuasan Ibu Menyusui dengan Pemberian Metode SPEOS (Stimulasi Pijat Endorphin, Oksitosin dan Sugestif) di Wilayah Kerja Puskesmas Tejakula I Tahun 2022 - Luh Astini Dewi; Ni Wayan Armini; Ni Gusti Kompiang Sriasih (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2023)
The success of exclusive breastfeeding is determined in early breastfeeding. Many mothers feel dissatisfied in breastfeeding because the breastmilk is no initial or non fluent. The purpose of this research is to determine the difference of maternal breastfeeding satisfaction before and after giving the SPEOS method. The research method is quasi-experimental and use two groups pretest posttest design. The sample is 18 mothers in intervention group and 18 mothers in control group by using purpossive sampling. Measurement of maternal breastfeeding satisfaction use the MBFES tool. The data distribution is normal and the data analysis use Dependent T-Test and Independent T-Test with α=0,05. The result of this research is there is defference maternal breastfeeding satisfaction before and after giving the SPEOS method (p value<0,001), there is difference before and after giving convensional care (p value=0,012), there is no difference maternal breastfeeding satisfaction before treatment in intervention and control group (p value=0,156), there is difference maternal breastfeeding satisfaction before treatment in intervention and control group (p value<0,001). Giving SPEOS method make mothers feel confident and relax and can increase the breastmilk production. It is suggested giving SPEOS method to the early breastfeeding mother for increasing the maternal breastfeeding satisfaction.